Identification of altered plasma proteins by proteomic study in valvular heart diseases and the potential clinical significance. - Ge Gao (Public Library of Science (PLoS), 2013)
Background Little is known about genetic basis and proteomics in valvular heart disease (VHD) including rheumatic (RVD) and degenerative (DVD) valvular disease. The present proteomic study examined the hypothesis that certain proteins may be associated with the pathological changes in the plasma of VHD patients. Methods and results Differential protein analysis in the plasma identified 18 differentially expressed protein spots and 14 corresponding proteins or polypeptides by two-dimensional electrophoresis and mass spectrometry in 120 subjects. Two up-regulated (complement C4A and carbonic anhydrase 1) and three down-regulated proteins (serotransferrin, alpha-1-antichymotrypsin, and vitronectin) were validated by ELISA in enlarging samples. The plasma levels (n = 40 for each) of complement C4A in RVD (715.8±35.6 vs. 594.7±28.2 ng/ml, P = 0.009) and carbonic anhydrase 1 (237.70±15.7 vs. 184.7±10.8 U/L, P = 0.007) in DVD patients were significantly higher and that of serotransferrin (2.36±0.20 vs. 2.93±0.16 mg/ml, P = 0.025) and alpha-1-antichymotrypsin (370.0±13.7 vs. 413.0±11.6 µg/ml, P = 0.019) in RVD patients were significantly lower than those in controls. The plasma vitronectin level in both RVD (281.3±11.0 vs. 323.2±10.0 µg/ml, P = 0.006) and DVD (283.6±11.4 vs. 323.2±10.0 µg/ml, P = 0.011) was significantly lower than those in normal controls. Conclusions We have for the first time identified alterations of 14 differential proteins or polypeptides in the plasma of patients with various VHD. The elevation of plasma complement C4A in RVD and carbonic anhydrase 1 in DVD and the decrease of serotransferrin and alpha-1-antichymotrypsin in RVD patients may be useful biomarkers for these valvular diseases. The decreased plasma level of vitronectin - a protein related to the formation of valvular structure - in both RVD and DVD patients might indicate the possible genetic deficiency in these patients.